No benefit of continuing vs stopping 5‐aminosalicylates in patients with ulcerative colitis escalated to anti‐metabolite therapy. Issue 3 (23rd June 2020) - Singh, Siddharth; Kim, Jihoon; Zhu, Wenhong; Dulai, Parambir S.; Sandborn, William J.; Jairath, Vipul
Summary: Background: Whilst continuation of 5‐aminosalicylates (5‐ASA) after escalation to biologic therapy is considered ineffective in patients with ulcerative colitis (UC), their role in patients escalated to anti‐metabolites is unclear. Aim: To compared patterns and outcomes of continuing vs stopping 5‐ASA in patients with UC who escalated to anti‐metabolite monotherapy, using a de‐identified administrative claims database. Methods: We identified patients with UC who were new users of anti‐metabolite monotherapy who were receiving 5‐ASA, and were followed for at least 12 months after starting anti‐metabolite therapy. We evaluated patterns of 5‐ASA use (stopped 5‐ASA, short‐term 5‐ASA use for <6 months after starting anti‐metabolites, persistent 5‐ASA use for >6 months after starting anti‐metabolites). We compared outcomes (risk of UC‐related hospitalisation and/or surgery, need for corticosteroids, treatment escalation to biologic therapy) by pattern of 5‐ASA use, using Cox proportional hazard analysis adjusting for age, sex, race, comorbidity burden, and hospitalisation or emergency department visit, abdominal surgery and corticosteroid use in the previous 12 months (as measures of disease severity), with a 12‐month immortal time period. Results: Of 4068 patients with UC who were new‐users of anti‐metabolite monotherapy, 578 (14.2%), 782 (19.2%) and 2708 (66.6%) stopped 5‐ASA, used 5‐ASA transiently or persistently, respectively. Compared to patients who stopped 5‐ASA after starting anti‐metabolites, persistent 5‐ASA use was associated with a higher risk of UC‐related hospitalisation (HR, 1.40 [1.07‐1.83]) and corticosteroid use (HR, 1.48 [1.28‐1.70]), without an increase in risk of UC‐related surgery (HR, 1.32 [0.86‐2.00]) or treatment escalation (HR, 0.80 [0.53‐1.20]). Sensitivity analyses using a 3 months window after initiation of anti‐metabolites to classify patients as continuing vs stopping 5‐ASA showed similar results. Residual confounding by disease severity could not be excluded. Conclusion: 5‐ASA are usually continued long‐term even after escalating to anti‐metabolite therapy in patients with UC without clinical benefit.